The Correlation between Self-Confidence with Career Planning at Santri Pesantren Nurul Yaqin Ambung Kapur Padang Pariaman - Resi Syahber Alfitrah; Taufik Taufik (Universitas Negeri Padang, 2021)
This research is based on the fact that self-confidence is an important thing that must be owned by every individual, because with high self-confidence it will make it easier for someone to do all things, because they believe in themselves and know their own strengths and weaknesses, therefore Students who have been in high school who are about to graduate must have high self-confidence to make it easier for them in career planning after graduation. Good career planning for students will make it easier for them to determine their future careers. This study aims to determine the relationship between self-confidence and career planning in PesantrenNurulYaqinAmbungKapur Padang Pariaman. The subjects in this study were 84 students of the Islamic boarding school Nurul Yaqin Ambung Kapur Padang Pariaman from class XI 44 people and class XII 40 people. The type in this research is descriptive correlational. Data were collected using a scale of self-confidence and career planning scale Likert scale model. The data were processed using the percentage technique and Pearson product moment correlation. The results of the data analysis of this study indicate that: (1) most of the santri had high self-confidence as much as 75%, (2) most of the santri had good career planning as much as 80%. The correlation coefficient value obtained in this study was 0.530 with an error rate of <0.05. This shows that there is a significant positive relationship in the moderate category between self-confidence and career planning for the students.